Desain Media Pembelajaran Berbasis Aplikasi Android untuk Pelajaran Fiqih Materi Waris Kelas XI Madrasah Aliyah - Hariman Surya Siregar; Miftahul Fikri; Firmansyah (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to design an android-based learning media using the Kodular web site for class XI students at MAN 1 Garut and to determine the feasibility of learning media based on android applications. This research is a research and development (R&D) adapted and modified from the 4D development model developed by Thiagarajan. Activities at each stage of development are: definition stage, design stage, development stage, and dissemination stage. Based on the research results, it is known that: 1) Android Application-Based Learning Media Development is carried out in 4 stages, namely: a) Preliminary study; b) Design; c) Development; and d) Trial and evaluation. 2) Android Application-Based Learning Media is feasible to use based on the assessment of: a) Material experts obtained results of 88.97% (very feasible); and b) Media experts got a result of 84.60% (very decent). 3) Student assessment of small group trial learning media obtained results of 83.13% (very feasible) and field tests obtained results of 87.48% (very feasible). The conclusion of this study is that the learning media received a very positive response from students.